2015
DOI: 10.2967/jnumed.114.153502
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Evaluation of Auger Electron–Emitting Theranostic Radionuclides

Abstract: Several radionuclides used in medical imaging emit Auger electrons, which, depending on the targeting strategy, either may be exploited for therapeutic purposes or may contribute to an unintentional mean absorbed dose burden. In this study, the virtues of 12 Auger electron-emitting radionuclides were evaluated in terms of cellular S values in concentric and eccentric cell-nucleus arrangements and by comparing their dose-point kernels. Methods: The Monte Carlo code PENELOPE was used to transport the full partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 29 publications
1
44
1
Order By: Relevance
“…MCNP is based on Monte Carlo simulation and allows the transport of radiation through a 3-dimensional geometry, whereas MIRDcell uses the analytic method and propagates electrons in straight trajectories. Falzone et al found that when the source was farther from the target region, the difference between cellular S values for Augeremitting radionuclides calculated from PENELOPE Monte Carlo simulation and the MIRD method tended to increase (25).…”
Section: Discussionmentioning
confidence: 99%
“…MCNP is based on Monte Carlo simulation and allows the transport of radiation through a 3-dimensional geometry, whereas MIRDcell uses the analytic method and propagates electrons in straight trajectories. Falzone et al found that when the source was farther from the target region, the difference between cellular S values for Augeremitting radionuclides calculated from PENELOPE Monte Carlo simulation and the MIRD method tended to increase (25).…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as high-resolution autoradiography or secondary ion mass spectrometry can quantitatively depict the distribution at the cellular level (31). This distribution may be used as input to derive the absorbed dose with Monte Carlo codes (32,33). Uniform distribution, as considered in the present study, is an acceptable model for some molecules, which are internalized via receptor-mediated endocytosis and partly trafficked to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the calculated and MIRD values could be attributed to different calculation approaches: in MIRD electrons propagate in straight trajectories, whereas MCNP6 also takes into account the straggling energy losses [3]. Moreover, the MIRD spectra could be different from the ICRP-107 ones.…”
Section: S-values Resultsmentioning
confidence: 99%
“…Even if α-emitters have the potential for molecular targeted radiotherapy, Auger electrons could have a reduced crossfire effect, given the extremely localized energy deposition [3]. Several Auger-emitter radionuclides have been studied and proposed for molecular targeted radiotherapy [3]. Among the Auger-emitter radionuclides, 125 I is of particular interest, as it emits about 23 electrons per decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation